Atlas of Lymphatic Anatomy in the Head, Neck, Chest and Limbs - Pan, Wei-Ren (Springer Singapore : Imprint: Springer, 2017)
This atlas provides detailed information on the human lymphatic system in the head, neck and chest regions as well as the extremities, with more than 400 photographs and radiographs, including micro and macro views of the morphology. Much of the content is presented for the first time, such as the individual differences in lymphatic distribution, especially in the head neck region; characteristics of the indirect precollecting lymph vessel in the scalp; the lymphatic ampulla and diverticulum; and the transparent lymph node. Providing insights into the lymphatic anatomy, the book is an essential resource for medical and science students as well as therapists, clinicians and researchers working in this field.
Keywords: Medicine.; Human anatomy.; elektronické knihy; electronic books